2016
DOI: 10.2967/jnumed.116.177584
|View full text |Cite
|
Sign up to set email alerts
|

NAMPT Inhibitor GMX1778 Enhances the Efficacy of177Lu-DOTATATE Treatment of Neuroendocrine Tumors

Abstract: Neuroendocrine tumors (NETs) can be treated by peptide receptor radionuclide therapy using radiolabeled somatostatin analogs. However, the efficacy of such treatment is low and needs to be optimized. Our study evaluated the potential radiosensitizing effects of inhibition of nicotineamide phosphoribosyltransferase on 177 Lu-DOTATATE treatment in a NET model. Methods: Nude mice xenografted with the human NET cell line GOT1 were treated with semiefficient doses of 177 Lu-DOTATATE (7.5 MBq, intravenously) or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…To improve the therapeutic efficacy of PRRT in NETs, different strategies have been investigated as follows: several clinical studies using fluoropyrimidine-based chemotherapy regimens for PRCRT in NET patients (3,(5)(6)(7)(8), preclinical studies using epigenetic modifiers as DNMT inhibitors/HDAC inhibitors to upregulate SSTR expression (12,13) and radioligand binding (12,13), preclinical studies using novel molecular target compounds for PRCRT (17)(18)(19), and variation of radiopharmaceuticals by the use of the a-emitters 215 Act or 213 Bis (20) or by the use of somatostatin antagonists (21). In preclinical studies, Taelman et al (12) and Veenstra et al (13) reported that several DNMT inhibitors and HDAC inhibitors induce SSTR mRNA transcription and protein expression and enhance specific SSTR-mediated radioligand binding of NET cells.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the therapeutic efficacy of PRRT in NETs, different strategies have been investigated as follows: several clinical studies using fluoropyrimidine-based chemotherapy regimens for PRCRT in NET patients (3,(5)(6)(7)(8), preclinical studies using epigenetic modifiers as DNMT inhibitors/HDAC inhibitors to upregulate SSTR expression (12,13) and radioligand binding (12,13), preclinical studies using novel molecular target compounds for PRCRT (17)(18)(19), and variation of radiopharmaceuticals by the use of the a-emitters 215 Act or 213 Bis (20) or by the use of somatostatin antagonists (21). In preclinical studies, Taelman et al (12) and Veenstra et al (13) reported that several DNMT inhibitors and HDAC inhibitors induce SSTR mRNA transcription and protein expression and enhance specific SSTR-mediated radioligand binding of NET cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tateishi et al reported that NAMPT inhibitor conferred metabolic susceptibility in IDH1 mutant gliomas [35]. The NAMPT inhibitor GMX1778 also enhanced the efficacy of radiolabeled somatostatin analog 177 Lu-DOTATATE treatment and induces a prolonged antitumor response [36]. …”
Section: Introductionmentioning
confidence: 99%
“…A similar approach successfully tested in vivo is the combination of PRRT with a nicotineamide phosphoribosyltransferase (NAMPT) inhibitor that blocks nicotinamide-adenine-dinucleotide (NAD + ) regeneration after consumption by PARP. The NAMPT inhibitor GMX1778 produced a synergistic antitumor effect on GOT1 xenografts in mice treated with PRRT (Elf et al 2017). Furthermore, a preclinical study showed that Hedgehog inhibitors can function as radiosensitisers of PRRT.…”
Section: Radiosensitisationmentioning
confidence: 97%